南极中山站排污口土壤中微生物群落的DGGE分析 - 林曦; 曾润颖 (2008)
以南极中山站排污口土壤为研究对象,提取样品中微生物宏基因组DNA,用变性梯度凝胶电泳(DGGE)对宏基因组DNA中的16SrRNA基因V3可变区进行分析,测定了31个不同条带所代表的序列.比较结果显示,排污口土壤样品与相同生境对照样品中的微生物类群组成均以CFB(Cytophaga-Flexibacteria-Bacteroides)类群和γ-变形菌纲(γ-Proteobacteria)为主,另外还有少量的α-,β-,δ-变形菌纲,和一些原核的藻类和革兰氏阳性细菌(G+).但在排污口土壤样品中检出了传染性微生物毛球菌属(Trichococcus)和狡诈菌属(Dolosigranulum),以及丰富的小球藻(Chlorella),说明污水的排放已经对该地微生物群落造成明显的影响. The study of Antarctic microbial ecology plays a key role in the understanding of the human-caused impacts on Antarctic environment. In this study, an investigation was conducted on the microbial community in the sewage contaminated soil in the Zhongshan Station, Antarctic. Metagenome DNA was directly extracted and purified from the samples. Denaturing gradient gel electrophoresis (DGGE) was used to analyze the V3 region of 16S rRNA gene. A total of 31 bands were separated from denaturing gradient gel and sequenced. The results of sequence comparison showed that the microbial community in both sewage contaminated soil and normal soil samples were all mainly consisted of CFB group and γ-proteobacteria, as well as other minor microorganisms including α-, β-, δ-proteobacteria, algae and low G+C Gram positive (G+) bacteria. However, the enriched Chlorella and the existed infective pathogens (Trichococcus pasteurii and Dolosigranulum pigrum) in the sewage contaminated soil obviously indicated that sewage discharge had already affected the microbial community in this area. 国家自然科学青年基金资助项目(No.40406029)~